Juridical Analysis Of Proof Elements Harm State Finance In Criminal Actions Corruption In Indonesia - Andre Yosua M; Tegar Mulia (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Policies that are often taken by public officials sometimes give rise to major criticism committing a pattern of criminal acts of corruption. Policies that are considered can fall into the action category corruption is policies that could harm state finances. So it's a loss State finances are one of the elements of criminal acts of corruption in Article 2 paragraph (1) and Article 3 Act No. 31 Year 1999 jo Act No. 20 Year 2001 about Eradication Act Criminal Corruption. The formulation of elements that are detrimental to state finances in these two articles is at the evidentiary level still raises various obstacles because it is an unclear and unclear norm multiple interpretations. Results from study show that prove that element harm state finances in criminal acts of corruption are still understood as formal criminal acts so that the proof Enough with fulfil deed the And No need There is consequence, Good Which potential harm finance country nor loss Which Actually, perpetrator can convicted. After Court Constitution through Decision Number 25/PUU-XIV/2016 mention that the word